Budget, motives and strategies for financial independence of undergraduates - Diachkova, Anna V.; Avramenko, Elena S.; Melikova, Mavzuna Kh (Economic consultant, 2020)
Introduction. The problems of scientific analysis, where the subject of study is the financial independence of undergraduates, mainly focuses on two directories: the study of the academic performance of undergraduate and the factors affecting it; financial condition of undergraduate depending on tuition fees. In modern studies, the issues of financial independence of students, their budget are not given due attention. The employment of students is often seen as one of the factors that negatively affect their academic performance, or in the context of forced work caused by high tuition fees. In today's pandemic realities, the aspect of the financial independence of students is actualized, while the problem of students' labor activity during training is of scientific and practical interest as a forced measure to maintain their well-being in order to gain financial independence. Materials and methods. The survey was attended by: 2-4-year students of the Bachelor's degree program "Applied Economics and Finance" (38.03.01 Economics) of the Institute of Economics and Management of Ural Federal University was carried out. The total number of students in 2-4 courses on the program is 284. Results and discussion. As a result of the study, the key motives for obtaining financial independence have been identified, which boil down either to the forced need to find finances, or to the desire to obtain financial independence and the formation of labor and financial competencies; formulated the basic financial strategies of students in relation to budget planning, budget optimization - passive as an orientation towards transfers from parents and the state, active as a search for grant support or going to work; it was found that the problem of choosing between work and study as an additional criterion included opportunity costs, measured as deterioration in academic performance; it was found that significant financial support from parents (family) and its increase with an increase in student spending forms a "soft budget constraint" for a student, reducing the motivation to gain financial independence. It was founded that more than 20% of 2-4-year students have part-time gob, while 2/3 of the working students do not “sacrifice” their studies for work. This is due to the fact that the motivation for choosing a job is voluntary. The survey data allowed to conclude that students are focused both on the improving of labor and financial competencies. It was revealed that the main source of income for their budget is transfers from parents (more than 90%) but own earns are less than 6% of the student budget. It should be noted that there was a large range in the students’ income: from 2,500 to 36,000 rubles. This may be due to both the income of the family in which the student lives and the model of financial support of the parents: they admit the independence of students according to their budget or the autonomy of their student children is practically absent. Conclusion. The results of this study are aimed at comprehending the educational, scientific, labor activity of a student, taking into account the motives for obtaining financial independence, which can be taken into account in the design of individual educational trajectories of students, the development of grant projects and offers of internship, educational loans, which together ensure the strengthening of the financial independence of students.